Pendampingan Pengembangan Pembelajaran Berbasis Case Method dan Tim Based Project Musyawarah Guru Mata Pelajaran (MGMP) Pendidikan Jasmani Olahraga dan Kesehatan Sekolah Menengah Pertama Kota Medan - Suryadi Damanik; Ibrahim; Usman Nasution; Saipul Ambri Damanik; Risky Efriana Saragih (Jurnal Bina Pengabdian Kepada Masyarakat, 2022)
Case method is a problem-based learning method, which aims to make the learning process more concrete, and can develop students' abilities in critical thinking, creative, innovative and problem solving. Team Based Project is a project-based learning method that starts with a problem. Through Team Based Project students are required to work on real projects through the process of exploration, analysis, synthesis, assessment, investigation and collaboration to produce real work. Learning with Team Based Project will be able to develop active learning and develop students' ability, critical thinking, creative, collaborative and innovative. The methods that will be used to achieve the objectives of Community Service activities are, mentoring, training, providing facilities, and empowerment with the following stages: 1) Preparation Stage; 2) Assessment stage; 3) Alternative Program or Activity Planning Phase; 4) Action Plan Formulation Phase; 5) Program or Activity Implementation Phase; and 6) Evaluation Phase. The results of the Community Partnership Program activities that will be carried out at the Teacher's Meeting of Physical Education and Sports Subjects are to provide knowledge and skills in the development of Physical Education and Sports Education learning. This activity aims to: 1) increase partners' knowledge about Case Methods and Team Based Projects, 2) improve partners' abilities in creative, innovative, professional, and independent abilities, 3) improve partners' abilities in developing Case Method and Team Based Project-based Sports and Health Physical Education learning in Indonesia Junior High School, 4) partners have learning tools for Physical Education, Sport and Health based on Case method and Team based projects in accordance with basic competencies.